2022
DOI: 10.3389/fmicb.2022.906920
|View full text |Cite
|
Sign up to set email alerts
|

Akkermansia muciniphila Alters Gut Microbiota and Immune System to Improve Cardiovascular Diseases in Murine Model

Abstract: The gut microbiota plays an important role in a variety of cardiovascular diseases. The probiotics screened based on microbiota can effectively improve metabolism and immune function of the body, which is of great value in the field of cardiovascular disease treatment. Abdominal aortic aneurysms (AAA) refer to the lesion or injury of the abdominal aortic wall resulting in a localized bulge, which is one of the cardiovascular diseases with pulsing mass as the main clinical symptom. Previous studies have confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Based on current scientific evidence, diet-induced metabolic endotoxemia can impair the gut integrity, leading to an inhibited growth of A. muciniphila. Increased abundance of A. muciniphila was associated with restoration of gut barrier function and prevention of adipose inflammation against HFD-mediated metabolic endotoxemia. , Since acetate producing Oscillospiraceae is directly associated with A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on current scientific evidence, diet-induced metabolic endotoxemia can impair the gut integrity, leading to an inhibited growth of A. muciniphila. Increased abundance of A. muciniphila was associated with restoration of gut barrier function and prevention of adipose inflammation against HFD-mediated metabolic endotoxemia. , Since acetate producing Oscillospiraceae is directly associated with A.…”
Section: Resultsmentioning
confidence: 99%
“…56 Increased abundance of A. muciniphila was associated with restoration of gut barrier function and prevention of adipose inflammation against HFD-mediated metabolic endotoxemia. 56,57 Since acetate producing Oscillospiraceae is directly associated with A. muciniphila, BF supplementation at a high dose was shown to enhance their growth and hence the circulating acetate, resulting in improved insulin sensitivity of the host. 58−60 Furthermore, our results also indicated that BF supplementation can increase the abundance of Ruminococcaceae and Butyricicoccaceae (Figure 6F).…”
Section: Bf Extract Modulated the Composition Of Gut Microbiota In A ...mentioning
confidence: 99%
“…Previous studies have demonstrated that Akkermansia is a promising target for treating intestinal microbiota-related diseases, such as colitis, metabolic syndrome, and immune diseases (15). Recently, He et al (16) reported that Akkermansia muciniphila inhibited the formation of AAA by restoring gut microbiota diversity, and altered the expression of peripheral immune factors. Barnesiella intestinihominis is also regarded as a beneficial bacterium for host homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…[25] Different study shown that administration of A. muciniphila improved damage of the elastic fibers in the vascular wall, inhibited the infiltration of inflammatory cells and protected the integrity of the medial septum in the abdominal aorta of mice, indicating that A. muciniphila can inhibit the formation of aortic aneurysms in mice. [26] Nonalcoholic fatty liver disease (NAFLD) NAFLD is a chronic liver disease and a hepatic manifestation of the metabolic syndrome. The exact cause of NAFLD is unidentified, but it is thought to be linked with abnormal lipid metabolism associated with obesity and metabolic syndrome.…”
Section: Obesitymentioning
confidence: 99%